Bugs in danger : our vanishing bees, butterflies, and beetles - Kurlansky, Mark (Bloomsbury Children's Books, 2019)
Examines the mysterious colony collapse disorder currently threatening bee populations around the world, as well as threats to populations of other bugs, including beetles and butterflies. Investigates the history of the world's diverse bug populations and tracks the events and changes--from farmers importing ladybugs for crop control to how bees evolved to pollinate specific plants--and how they have contributed to the current population crisis.